Continuous Suprainguinal Fascia Iliaca Block for Postoperative Analgesia Management After Hip and Knee Arthroplasty Surgeries: A Report of Two Cases - Demir, Ufuk; Taşkın, Öztürk; Yılmaz, Ayşe; Tanyıldızı Küçük, Büşra; Doğanay, Zahide (Springer Science and Business Media LLC, 2025)
Knee and hip arthroplasty are common orthopedic procedures that are frequently associated with moderate to severe postoperative pain. Regional anesthesia techniques play a crucial role in multimodal analgesia strategies for managing postoperative pain. The suprainguinal fascia iliaca (SIFI) block is an effective regional anesthesia technique frequently used for postoperative analgesia in lower extremity surgeries, including knee and hip arthroplasty. These techniques can be safely applied either as a single-shot injection or via continuous catheter insertion. In this case report, we describe our experience with the use of continuous SIFI block for postoperative analgesia in knee and hip arthroplasty.
Keywords: Anesthesiology